Assessment of Oral Cancer Awareness Among Medical Professionals Working in Bergama District of Izmir Province, Turkey - NAMDAR PEKİNER, FİLİZ MEDİHA; KESER, GAYE (WOLTERS KLUWER MEDKNOW PUBLICATIONS, 2021)
Introduction: The aim of this study is to assess awareness of oral cancer in a group of medical professionals working in Bergama district of Izmir province, Turkey. Materials and Methods: The study group consisted of 90 medical doctors and a questionnaire was submitted to the study group consisting of 25 questions related to risk factors and screening methods, attitude toward oral cancer, control of oral cancer care, and knowledge on oral cancer. Results: All participants regard the use of cigarettes and viral diseases as a risk factor and 95.6% of them consider the use of alcohol as a risk factor. 15.6% of all participants reported erythroplakia and Morbus Bowen as two lesions with the greatest cancerous tendency, while 47.8% of participants reported leukoplakia and erythroplakia. Among age groups, rates of assessment of alcohol usage as a risk factor (P = 0.002), rates of assessment of high age as a risk factor (P = 0.007), rates of distribution of the most prevalent oral cancer regions (P = 0.001), rates of distribution of the two lesion groups with the greatest sensitivity to cancer (P = 0021), and rates of assessment of prior alcohol use of the patient when taking medical history (P = 0.008) were statistically significant. Conclusion: The ability of medical professionals to recognize and diagnose oral cancer as early as possible concerning diagnostic and treatment progress is a very crucial point. This study suggests that medical doctors show a sensitive attitude toward oral cancers. However, it also reveals that there is a need for improvement of the undergraduate curriculum in oral cancer in medical schools and for the provision of postgraduate and continuing education on this topic.
Keywords: Awareness; medical professionals; oral cancer; PRIMARY-CARE PHYSICIANS; CAROLINA DENTISTS; KNOWLEDGE; ATTITUDES; DIAGNOSIS; OPINIONS; DELAYS